Analisis Diskriptif Technologi Acceptance Model pada Penerapan Blended Learning - Elistya Rimawati; Wawan Laksito Yuly Saptomo (Jurnal Ilmiah SINUS, 2019)
The Blended Learning learning model is a system that collaborates classroom face-to-face learning with online learning. This study aims to measure the acceptance of the Blended Learning learning model among students. The variables developed refer to the Technology Acceptance Model (TAM), which is a model of user acceptance of information systems. The data obtained were analyzed by descriptive statistics and qualitative analysis. The results showed that in general the use of the Blended Learning learning model could be accepted by students in the category of Good approaching is Very Good. The mean value of all aspects reached a value of 3.94 on a scale of 5 (79%). The results of qualitative analysis were in line with the results of quantitative analysis. Students received good use of e-Learning while maintaining face-to-face learning activities in class. The results of this study can be used as a basis for recommending the selection of learning methods in universities